Host Kinase Activity is Required for Coxiella burnetii Parasitophorous Vacuole Formation - Hussain, S. Kauser; Broederdorf, Laura J.; Sharma, Uma M.; Voth, Daniel E. (Frontiers in Microbiology, 2010)
Coxiella burnetii is the etiologic agent of human Q fever and targets alveolar phagocytic cells in vivo wherein the pathogen generates a phagolysosome-like parasitophorous vacuole (PV) for replication. C. burnetii displays a prolonged growth cycle, making PV maintenance critical for bacterial survival. Previous studies showed that C. burnetii mediates activation of eukaryotic kinases to inhibit cell death, indicating the importance of host signaling during infection. In the current study, we examined the role of eukaryotic kinase signaling in PV establishment. A panel of 113 inhibitors was analyzed for their impact on C. burnetii infection of human THP-1 macrophage-like cells and HeLa cells. Inhibition of 11 kinases or two phosphatases altered PV formation and prevented pathogen growth, with most inhibitor-treated cells harboring organisms in tight fitting phagosomes, indicating kinase/phosphatase activation is required for PV maturation. Five inhibitors targeted protein kinase C (PKC), suggesting a critical role for this protein during intracellular growth. The PKC-specific substrate MARCKS was phosphorylated at 24 h post-infection and remained phosphorylated through five days post-infection, indicating prolonged regulation of the PKC pathway by C. burnetii. Infection also altered the activation status of p38, myosin light chain kinase, and protein kinase A, suggesting C. burnetii subverts numerous phosphorylation cascades. These results underscore the importance of intracellular host signaling for C. burnetii PV biogenesis.